2020
DOI: 10.1172/jci131335
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor c-Maf is a checkpoint that programs macrophages in lung cancer

Abstract: Macrophages have been linked to tumor initiation, progression, metastasis, and treatment resistance. However, the transcriptional regulation of macrophages driving the protumor function remains elusive. Here, we demonstrate that the transcription factor c-Maf is a critical controller for immunosuppressive macrophage polarization and function in cancer. c-Maf controls many M2-related genes and has direct binding sites within a conserved noncoding sequence of the Csf-1r gene and promotes M2-like macrophage-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 71 publications
3
126
0
Order By: Relevance
“…Elevated expression of MafB in TAMs was also demonstrated in a mouse model of breast cancer [105]. A recent study found that M2 macrophages induced by IL-4 and IL-13 express high levels of c-Maf that regulates expression of M2-related genes (IL-12, IL-1b, IL-6, ARG1, IL-10, VEGF, TGFb, IRF4, and CCR2) [106]. c-Maf is expressed by TAMs in human non-small cell lung carcinoma (NSCLC), and promotes M2-mediated T cell suppression and tumor progression by controlling M2-related genes in vivo [106].…”
Section: Mafmentioning
confidence: 89%
“…Elevated expression of MafB in TAMs was also demonstrated in a mouse model of breast cancer [105]. A recent study found that M2 macrophages induced by IL-4 and IL-13 express high levels of c-Maf that regulates expression of M2-related genes (IL-12, IL-1b, IL-6, ARG1, IL-10, VEGF, TGFb, IRF4, and CCR2) [106]. c-Maf is expressed by TAMs in human non-small cell lung carcinoma (NSCLC), and promotes M2-mediated T cell suppression and tumor progression by controlling M2-related genes in vivo [106].…”
Section: Mafmentioning
confidence: 89%
“…Of interest, in the 3d injured nerve, Mac1, Mac3, and Mac4 strongly express the TFs Maf/c-Maf and Mafb/MafB. MafB promotes reprogramming of macrophages into an M2-like phenotype (Kim, 2017) and c-Maf is a checkpoint that programs Mac and is critical for the acquisition of an immunosuppressive phenotype (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both KLF4 and c-Myc, which have been implicated in pluripotent stem cell reprogramming (45), are ERK5 targets (46,47). However, a recent study showed that cMaf was a transcriptional regulator of protumoral macrophage activation (48). In the future, unbiased transcriptomic studies to establish the transcriptional network downstream of ERK5 will be essential to understand how ERK5 maintains proliferative protumor macrophage populations to support tumor progression and malignancy.…”
Section: Discussionmentioning
confidence: 99%